ChemInform Abstract: Silica‐Supported Tripod Triarylphosphines: Application to Palladium‐Catalyzed Borylation of Chloroarenes. Issue 3 (January 2015) - Iwai, Tomohiro; Harada, Tomoya; Tanaka, Ryotaro; Sawamura, Masaya
Abstract The presented system is applicable to one‐pot biaryl synthesis of biphenyl derivative (V) via Miyaura borylation—Suzuki coupling sequence.